2003
DOI: 10.1097/00003226-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

MUC7 Expression in the Human Lacrimal Gland and Conjunctiva

Abstract: The mucin profile of the lacrimal gland resembles that of the salivary gland. Both RNA and protein corresponding to MUC7 are present in the normal human lacrimal gland. Reverse transcription-polymerase chain reaction indicates that other transcripts of MUC1, MUC4, and MUC5B are present as well. Ocular MUC7 is also produced by the conjunctival mucosa. The lacrimal gland, therefore, contributes not only to the aqueous component of tears but also, in concert with the conjunctiva, may contribute to the total pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 20 publications
4
49
0
1
Order By: Relevance
“…Similarly, our use of 2 different MUC7-specific antibodies on maximally loaded gels, with 10-fold more total tear protein than necessary for detection in the control secretion (saliva), confirms the findings of Jumblatt et al (Jumblatt et al, 2003) that the small soluble mucin MUC7, which is produced by lacrimal gland epithelia, is not present in human tear film. Since MUC5B and MUC7 proteins have been detected in lacrimal gland tissue (Paulsen et al, 2004), our data suggest that these two mucins are retained in the lacrimal gland where they may be produced and locally degraded.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, our use of 2 different MUC7-specific antibodies on maximally loaded gels, with 10-fold more total tear protein than necessary for detection in the control secretion (saliva), confirms the findings of Jumblatt et al (Jumblatt et al, 2003) that the small soluble mucin MUC7, which is produced by lacrimal gland epithelia, is not present in human tear film. Since MUC5B and MUC7 proteins have been detected in lacrimal gland tissue (Paulsen et al, 2004), our data suggest that these two mucins are retained in the lacrimal gland where they may be produced and locally degraded.…”
Section: Discussionsupporting
confidence: 87%
“…MUC5B and MUC7 message and protein have been found in human lacrimal gland tissue (Jumblatt et al, 2003;Paulsen et al, 2004); however, previous assays did not detect the mucins in tears (Gipson et al, 2001;Jumblatt et al, 2003). To more conclusively demonstrate their presence or absence in tears, two additional antibodies specific for each of these mucins were used to probe immunoblots of maximally loaded gels (100μg of total tear protein) from a sample of pooled tears (N = 17).…”
Section: Selection Of Specific Mucin Antibodies For Detection Of Mucimentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, MUC5AC is not only produced by the goblet cells of excretory ducts but also by some acinar cells of the lacrimal gland (51). PCR analysis indicated that MUC1, MUC4, and MUC5B are expressed in human lacrimal tissue, but no in situ hybridization analysis has been performed to confirm their localization (39). In humans, MUC16 is present in the whole lacrimal apparatus (36).…”
Section: Muc Mrna Expression In Lacrimal Gland Acinar Cellsmentioning
confidence: 96%
“…Dry eye patients su®er from discomfort such as sensitivity to light, stinging, burning, blurriness, grittiness, or scratchy and itchy eye. [1][2][3] Such experiences could arise from the ocular surface due to changes in the quantity and quality of the overlaying tears. The multiple causes of dry eye make its diagnoses and treatment di±cult.…”
Section: Introductionmentioning
confidence: 99%